Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To factor the polynomial [tex]\( f(x) = x^5 - 5x^4 - 13x^3 + 65x^2 + 36x - 180 \)[/tex] completely, we are given that [tex]\( x = 5 \)[/tex] is a root. Knowing that [tex]\( x = 5 \)[/tex] is a root, we can factor out [tex]\( (x - 5) \)[/tex] from [tex]\( f(x) \)[/tex]. Let's proceed with the step-by-step factorization:
### Step 1: Polynomial Division
Since [tex]\( x = 5 \)[/tex] is a root of [tex]\( f(x) \)[/tex], [tex]\( x - 5 \)[/tex] is a factor of [tex]\( f(x) \)[/tex]. We perform polynomial division of [tex]\( f(x) \)[/tex] by [tex]\( x - 5 \)[/tex].
1. Setup the problem:
[tex]\( f(x) = x^5 - 5x^4 - 13x^3 + 65x^2 + 36x - 180 \)[/tex]
We divide this by [tex]\( x - 5 \)[/tex].
2. Perform polynomial division:
By synthetic division or long division, we divide the polynomial by [tex]\( x - 5 \)[/tex]:
[tex]\[ \begin{array}{r|rrrrrr} 5 & 1 & -5 & -13 & 65 & 36 & -180 \\ \hline & 1 & 0 & -13 & 0 & 36 & 0 \\ \end{array} \][/tex]
We get the quotient as:
[tex]\[ x^4 - 13x^2 + 36 \][/tex]
So, we have:
[tex]\[ f(x) = (x - 5)(x^4 - 13x^2 + 36) \][/tex]
### Step 2: Factor the Quotient Polynomial
Next, we need to factor the quotient polynomial [tex]\( x^4 - 13x^2 + 36 \)[/tex].
We recognize it as a quadratic in terms of [tex]\( x^2 \)[/tex]. Let's rewrite [tex]\( x^4 - 13x^2 + 36 \)[/tex] as:
[tex]\[ y = x^2 \][/tex]
[tex]\[ y^2 - 13y + 36 \][/tex]
### Step 3: Solve the Quadratic [tex]\( y^2 - 13y + 36 \)[/tex]
To factor [tex]\( y^2 - 13y + 36 \)[/tex], we find the roots of the quadratic equation:
[tex]\[ y^2 - 13y + 36 = 0 \][/tex]
Solving for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{13 \pm \sqrt{13^2 - 4 \cdot 36}}{2} \][/tex]
[tex]\[ y = \frac{13 \pm \sqrt{169 - 144}}{2} \][/tex]
[tex]\[ y = \frac{13 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ y = \frac{13 \pm 5}{2} \][/tex]
So, we have:
[tex]\[ y = 9 \quad \text{or} \quad y = 4 \][/tex]
In terms of [tex]\( x \)[/tex],
[tex]\[ x^2 = 9 \quad \text{or} \quad x^2 = 4 \][/tex]
[tex]\[ x = \pm 3 \quad \text{or} \quad x = \pm 2 \][/tex]
### Step 4: Write the Final Factorization
Therefore, we can factor [tex]\( x^4 - 13x^2 + 36 \)[/tex] as:
[tex]\[ x^4 - 13x^2 + 36 = (x^2 - 9)(x^2 - 4) = (x - 3)(x + 3)(x - 2)(x + 2) \][/tex]
### Step 5: Combine All Factors
Taking all the factors into account, the completely factored form of [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = (x - 5)(x - 3)(x - 2)(x + 2)(x + 3) \][/tex]
So, the polynomial [tex]\( f(x) \)[/tex] is factored completely as:
[tex]\[ f(x) = (x - 5)(x - 3)(x - 2)(x + 2)(x + 3) \][/tex]
### Step 1: Polynomial Division
Since [tex]\( x = 5 \)[/tex] is a root of [tex]\( f(x) \)[/tex], [tex]\( x - 5 \)[/tex] is a factor of [tex]\( f(x) \)[/tex]. We perform polynomial division of [tex]\( f(x) \)[/tex] by [tex]\( x - 5 \)[/tex].
1. Setup the problem:
[tex]\( f(x) = x^5 - 5x^4 - 13x^3 + 65x^2 + 36x - 180 \)[/tex]
We divide this by [tex]\( x - 5 \)[/tex].
2. Perform polynomial division:
By synthetic division or long division, we divide the polynomial by [tex]\( x - 5 \)[/tex]:
[tex]\[ \begin{array}{r|rrrrrr} 5 & 1 & -5 & -13 & 65 & 36 & -180 \\ \hline & 1 & 0 & -13 & 0 & 36 & 0 \\ \end{array} \][/tex]
We get the quotient as:
[tex]\[ x^4 - 13x^2 + 36 \][/tex]
So, we have:
[tex]\[ f(x) = (x - 5)(x^4 - 13x^2 + 36) \][/tex]
### Step 2: Factor the Quotient Polynomial
Next, we need to factor the quotient polynomial [tex]\( x^4 - 13x^2 + 36 \)[/tex].
We recognize it as a quadratic in terms of [tex]\( x^2 \)[/tex]. Let's rewrite [tex]\( x^4 - 13x^2 + 36 \)[/tex] as:
[tex]\[ y = x^2 \][/tex]
[tex]\[ y^2 - 13y + 36 \][/tex]
### Step 3: Solve the Quadratic [tex]\( y^2 - 13y + 36 \)[/tex]
To factor [tex]\( y^2 - 13y + 36 \)[/tex], we find the roots of the quadratic equation:
[tex]\[ y^2 - 13y + 36 = 0 \][/tex]
Solving for [tex]\( y \)[/tex]:
[tex]\[ y = \frac{13 \pm \sqrt{13^2 - 4 \cdot 36}}{2} \][/tex]
[tex]\[ y = \frac{13 \pm \sqrt{169 - 144}}{2} \][/tex]
[tex]\[ y = \frac{13 \pm \sqrt{25}}{2} \][/tex]
[tex]\[ y = \frac{13 \pm 5}{2} \][/tex]
So, we have:
[tex]\[ y = 9 \quad \text{or} \quad y = 4 \][/tex]
In terms of [tex]\( x \)[/tex],
[tex]\[ x^2 = 9 \quad \text{or} \quad x^2 = 4 \][/tex]
[tex]\[ x = \pm 3 \quad \text{or} \quad x = \pm 2 \][/tex]
### Step 4: Write the Final Factorization
Therefore, we can factor [tex]\( x^4 - 13x^2 + 36 \)[/tex] as:
[tex]\[ x^4 - 13x^2 + 36 = (x^2 - 9)(x^2 - 4) = (x - 3)(x + 3)(x - 2)(x + 2) \][/tex]
### Step 5: Combine All Factors
Taking all the factors into account, the completely factored form of [tex]\( f(x) \)[/tex] is:
[tex]\[ f(x) = (x - 5)(x - 3)(x - 2)(x + 2)(x + 3) \][/tex]
So, the polynomial [tex]\( f(x) \)[/tex] is factored completely as:
[tex]\[ f(x) = (x - 5)(x - 3)(x - 2)(x + 2)(x + 3) \][/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.